Levodopa Response in Patients With Early Parkinson Disease: Further Observations of the LEAP Study. (24th January 2023) - Frequin, Henrieke L.; Schouten, Jason; Verschuur, Constant V.M.; Suwijn, Sven R.; Boel, Judith A.; Post, Bart; Bloem, Bastiaan R.; van Hilten, Johannes J.; van Laar, Teus; Tissingh, Gerrit; Munts, Alexander G.; Dijk, Joke M.; et al.
Abstract : Background and Objectives: The Levodopa in EArly Parkinson's Disease (LEAP) study enabled us to conduct post hoc analyses concerning the effects of levodopa in patients with early Parkinson disease. Methods: The LEAP study was a double-blind, placebo-controlled, randomized, delayed-start trial in which patients with early Parkinson disease were randomized to receive levodopa/carbidopa 300/75 mg daily for 80 weeks (early-start group) or to placebo for 40 weeks followed by levodopa/carbidopa 300/75 mg daily for 40 weeks (delayed-start group). We analyzed the effect of levodopa with the Unified Parkinson's Disease Rating Scale on bradykinesia, rigidity, and tremor. At week 80, participants answered 3 questions regarding motor response fluctuations. Results: A total of 222 patients were randomized to the early-start group (mean ± SD age at baseline 64.8 ± 8.7 years; 71% male) and 223 to the delayed-start group (mean ± SD age at baseline 65.5 ± 8.8 years; 69% male). The difference between the early- and delayed-start groups in mean change from baseline to week 4, expressed as Hedges g effect size, was −0.33 for bradykinesia, −0.29 for rigidity, and −0.25 for tremor (for all symptoms indicating a small effect in favor of the early-start group); from baseline to week 22, respectively, −0.49, −0.36, and −0.44 (small to medium effect); and from baseline to week 40, respectively, −0.32, −0.19, and −0.27 (small effect). At 80 weeks, fewer patients in the early-start group (46 of 205 patients, 23%) experienced motor response fluctuations than patients in the delayed-start group (81 of 211, 38%; p < 0.01). Discussion: In patients with early Parkinson disease, levodopa improves bradykinesia, rigidity, and tremor to the same order of magnitude. For all 3 symptoms, effects were larger at 22 weeks compared with 4 weeks. At 80 weeks, there were fewer patients with motor response fluctuations in the group that had started levodopa earlier. Classification of Evidence: This study provides Class II evidence that the effect of levodopa on bradykinesia, rigidity, and tremor is larger after 22 weeks compared with 4 weeks of treatment. Trial Registration Information: ISRCTN30518857, EudraCT number 2011-000678-72.